Evaluation of pathogenic factors in reflux related gastritis. - Girardi, Gino; Trujillo, Raquel; Terra, Freddy; Lussheimer, Daniel; García Bianchi, Eduardo; Siécola, Osvaldo; Bonaba, Roberto; Meny, Miguel (Cirugía del Uruguay, 1987)
The effect of pathologic refiux of bile associated to pancreatic and duodenal juices on the gastric mucosa of dogs with diverse digestive reconstruction, bóth with intact or supressed vagal innervation, was studied.